Service Charge Administration in Commercial Properties: Governance and Operational Perspectives from Banex Plaza, Abuja - Komolafe, Markson Opeyemi; Komolafe, Abiemwense Lydia; Audu, Adedamola Fisayo; Tony, Ogheneovo Joy; Ankeli, Ikpeme Anthony; Olawuyi, Tolani Sayo; Nwodo, Geoffrey Ogbonna (NIU Journal of Social Sciences, 2026)
Service charge administration in multi-tenanted commercial properties represents a critical yet understudied dimension of property management governance in emerging markets. This study examines service charge administration at Banex Plaza, a major commercial complex in Abuja, Nigeria, using a sequential mixed-methods approach. The quantitative phase surveyed 162 tenants at the facility through systematic sampling of occupants, while the qualitative phase involved total enumeration of all five property and facilities managers (ESV1–ESV5) directly responsible for service charge administration in the plaza. Quantitative findings reveal pronounced governance deficiencies: 79 percent of tenants are not aware of the service charge components, while 82 percent do not understand how charges are apportioned. Consequently, 56.5 percent perceive administration as non-transparent and 81.5 percent deem cost allocation unfair. Service delivery dissatisfaction reaches 61.7 percent. Statistical analysis establishes a strong causal pathway wherein low awareness reduces transparency perception (r=0.58, p<0.001), which substantially determines service satisfaction (r=0.67, p<0.001). Qualitative findings illuminate underlying mechanisms: managers rely on verbal communication without documented systems, allocate charges through uniform floor-area methods without consumption metering, lack formal reserve funds for planned maintenance, and operate within fragmented regulatory environments. These constraints produce reactive rather than preventive maintenance systems and persistent tenant-management mistrust. The study concludes that service charge governance failures stem from systemic rather than isolated deficiencies, encompassing weak information disclosure, inadequate administrative systems, operational limitations, and regulatory fragmentation. The strong transparency–satisfaction relationship suggests that improved disclosure and accountability mechanisms can substantially enhance tenant satisfaction and compliance even when services are not substantially enhanced. The study recommends structured governance reforms including digital accounting systems, utility metering, formal reserve funds, tenant engagement structures, and standardized regulatory frameworks to address interconnected governance deficiencies in commercial property management. Keywords: Service Charge Administration, Transparency, Tenant Satisfaction, Cost Allocation, Commercial Real Estate, Nigeria.